A multi‐centre audit of excess steroid use in 1176 patients with inflammatory bowel disease. Issue 10 (26th September 2017) - Selinger, C. P.; Parkes, G. C.; Bassi, A.; Fogden, E.; Hayee, B.; Limdi, J. K.; Ludlow, H.; McLaughlin, S.; Patel, P.; Smith, M.; Raine, T.
Summary: Background: Corticosteroids are central to inducing remission in inflammatory bowel disease (IBD) but are ineffective maintenance agents. Aim: To benchmark steroid usage in British outpatients and assess factors associated with excess exposure. Methods: We recorded steroid use in unselected IBD outpatients. Cases meeting criteria for steroid dependency or excess were blind peer reviewed to determine whether steroid prescriptions were avoidable. Associations between steroid use and patient/institutional factors were analysed. Results: Of 1176 patients, 30% received steroids in the prior 12 months. 14.9% had steroid dependency or excess, which was more common in moderate/severe ulcerative colitis (UC) than Crohn's disease (CD) (42.6% vs 28.1%; P  = .027). Steroid dependency or excess was deemed avoidable in 49.1%. The annual incidence of inappropriate steroid excess was 7.1%. Mixed‐effects logistic regression analysis revealed independent predictors of inappropriate steroid excess. The odds ratio (OR, 95%CI) for moderate/severe compared to mild/quiescent disease activity was 4.59 (1.53‐20.64) for UC and 4.60 (2.21‐12.00) for CD. In CD, lower rates of inappropriate steroid excess were found in centres with an IBD multi‐disciplinary team (OR 0.62 [0.46‐0.91]), whilst dedicated IBD clinics protected against inappropriate steroid excess in UC (OR 0.64, 95% CI 0.21‐0.94). The total number of GI trainees was associated with rates of inappropriate steroid excess. Conclusions: Steroid dependency or excess occurred in 14.9% of British IBD patients (in 7.1% potentially avoidable). We demonstrated positive effects of service configurations (IBD multi‐disciplinary team, dedicated IBD clinics). Routine recording of steroid dependency or excess is feasible and should be considered a quality metric. Abstract : Linked Content This article is linked to Colizzo and Friedman and Selinger et al papers. To view these articles visithttps://doi.org/10.1111/apt.14334 andhttps://doi.org/10.1111/apt.14403 .